2013
DOI: 10.1002/cam4.132
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling upon 212Pb‐TCMC‐trastuzumab treatment in the LS‐174T i.p. xenograft model

Abstract: Recent studies have demonstrated that therapy with 212Pb-TCMC-trastuzumab resulted in (1) induction of apoptosis, (2) G2/M arrest, and (3) blockage of double-strand DNA damage repair in LS-174T i.p. (intraperitoneal) xenografts. To further understand the molecular basis of the cell killing efficacy of 212Pb-TCMC-trastuzumab, gene expression profiling was performed with LS-174T xenografts 24 h after exposure to 212Pb-TCMC-trastuzumab. DNA damage response genes (84) were screened using a quantitative real-time p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 25 publications
0
31
1
Order By: Relevance
“…Targeting LS-174T tumors with 212 Pb-trastuzumab increases DNA double-stranded breaks, impairs DNA damage repair, persistent G2/M arrest and chromatin remodeling. 9,10 HER2 is expressed by an array of epithelial cancers such as pancreas (35-45%), breast (25-30%), ovarian (25-100%) and colorectal (up to 90%). [11][12][13][14] Conversely, one might also state that HER2, for example, is not well expressed in 55-65% of pancreatic cancers, and therefore identification of additional molecular targets is warranted to expand the repertoire of a-targeted RIT.…”
Section: Introductionmentioning
confidence: 99%
“…Targeting LS-174T tumors with 212 Pb-trastuzumab increases DNA double-stranded breaks, impairs DNA damage repair, persistent G2/M arrest and chromatin remodeling. 9,10 HER2 is expressed by an array of epithelial cancers such as pancreas (35-45%), breast (25-30%), ovarian (25-100%) and colorectal (up to 90%). [11][12][13][14] Conversely, one might also state that HER2, for example, is not well expressed in 55-65% of pancreatic cancers, and therefore identification of additional molecular targets is warranted to expand the repertoire of a-targeted RIT.…”
Section: Introductionmentioning
confidence: 99%
“…Gene expression qRT-PCR array profiling after exposure to 212 Pb-TCMC-trastuzumab was recently reported from Yong et al In this study, 212 Pb-TCMC-trastuzumab treatment differentially regulated genes including genes involved in apoptosis ( ABL, GADD45a, GADD45r, PCBP4, and p73 ), Cell cycle ( ATM, DDIT3, GADD45a, GTSE1, MKK6, PCBP4, and SESN1 ), and damaged DNA binding (DDB) and repair (ATM, and BTG2). Furthermore, the p73/GADD45 signaling pathway mediated by p38 kinase signaling may be involved in the cellular response of tumors exposed to 212 Pb-TCMC-trastuzumab [12]. …”
Section: Mechanistic Studies Of Targeted 212pbmentioning
confidence: 99%
“…In pre-clinical studies, TAT using 212 Pb has shown significant therapeutic efficacy in both in vitro and in vivo model systems [1012]. A mechanistic study of 212 Pb-labeled TAT demonstrated significant impact of catastrophic dsDNA destruction as a result of high-LET 212 Pb traversal of the nucleus, with interference with DNA damage repair and perturbation of the cell cycle, leading to significant tumor cell killing [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Targeted α-radiation therapy has been shown to effect cell death through production of double-stranded DNA breaks, DNA crosslinking, chromosomal rearrangements, the induction of apoptosis, perturbation of the cell cycle, and blockage or downregulation of the DNA damage repair mechanism specific to double-stranded DNA breaks. 1014 …”
Section: Introductionmentioning
confidence: 99%